HUBUNGAN KEHILANGAN GIGI DENGAN STATUS GIZI PADA LANSIA DI PONDOK LANSIA TULUS KASIH KOTA BANDUNG (Poltekkes Kemenkes Bandung, 2023)
Tooth loss is one of the most common dental and oral health problems experienced by the Indonesian population. The highest proportion of tooth loss in Indonesia on 2018 was found in the elderly with the age group 65 years. Tooth loss in the elderly can affect nutritional intake. Masticatory disorders can occur in the elderly as a result of tooth loss and will result in food sorting by the elderly. As a result, the elderly can experience malnutrition and there will be a decrease in their nutritional status. The purpose of this study was to determine the relationship between tooth loss and nutritional status of the elderly at Pondok Lansia Tulus Kasih Bandung. The research method used is analytic with a cross sectional design. The subject of this research is the elderly who live at Pondok Lansia Tulus Kasih, Bandung. The sampling was done by purposive sampling technique and by calculating the Krejcie and Morgan formula so that the samples taken were 32 people. The category of nutritional status of the elderly who had the highest number of functional tooth loss was poor nutritional status with a percentage of 40%. And the nutritional status of the elderly who had the highest number of non-functional tooth loss was normal nutritional status (59.1%). The results of the Kendall's tau test showed p = 0.268 (p > 0.05). The results of this study showed that there was no relationship between tooth loss and nutritional status in the elderly at Pondok Lansia Tulus Kasih Bandung.